2022
DOI: 10.13005/bpj/2354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Therapeutic Effects of Wet Cupping (Al-Hijamah) on Hematological Parameters, Kidney Function Tests and Lipid Profile in Adult Women

Abstract: The purpose of this study is to evaluate the role of wet cupping in improving the kidney function tests, hematological parameters and lipid profile in adult women. Blood samples were collected and used for measuring uric acid, creatinine, urea, glucose, triglyceride, cholesterol, HDL cholesterol, LDL cholesterol and complete blood cell (CBC) counts. The necessary calculations were done to estimate the unmeasured parameters. The study subjects for body mass index showed that most of these women were overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…All those individuals who are willing to do their cupping therapy were included in the study whereas individuals who has done cupping therapy with in past 1 or 2 weeks and patients of cardiovascular, hypertension, diabetics, hemophilia and individual using blood thinner medication were excluded from the study. The sample size formula n (each group) =(Po q + p11q) (z1-α/2 +z1-β) 2 (p1 -qo) The value of alpha (1.98), The value of beta (0.84), Proportion of before cupping therapy (p0) (0.15), Proportion of after cupping therapy (p1) (0.25), Ratio of pre to post cupping therapy, n= ([(0.15*0.85) + (0.25*0.75)] * [1.96 + 0.84] ^2)/ (0.18-0.10) ^2 = (0.315*7.84)/0.01 = 210 (105 pre and 105 post cupping therapy). Convenient sampling technique was adopted.…”
Section: Methodsmentioning
confidence: 99%
“…All those individuals who are willing to do their cupping therapy were included in the study whereas individuals who has done cupping therapy with in past 1 or 2 weeks and patients of cardiovascular, hypertension, diabetics, hemophilia and individual using blood thinner medication were excluded from the study. The sample size formula n (each group) =(Po q + p11q) (z1-α/2 +z1-β) 2 (p1 -qo) The value of alpha (1.98), The value of beta (0.84), Proportion of before cupping therapy (p0) (0.15), Proportion of after cupping therapy (p1) (0.25), Ratio of pre to post cupping therapy, n= ([(0.15*0.85) + (0.25*0.75)] * [1.96 + 0.84] ^2)/ (0.18-0.10) ^2 = (0.315*7.84)/0.01 = 210 (105 pre and 105 post cupping therapy). Convenient sampling technique was adopted.…”
Section: Methodsmentioning
confidence: 99%
“…These ratios are commonly used as atherogenic indices in the literature [11]. Moreover, Ahmed et al [10] found no significant differences in the levels of TC, LDL-C, and HDL-C levels based on WC therapy durations (< 1 year or > 1 year). This contradicts the findings by Suhaily et al [11], and Alsafi [12] who reported a significant difference after 3 months of cupping therapy.…”
Section: Jarmentioning
confidence: 98%